Awesome orange birthday - Ruths, Mitali Banerjee (Ruths, Mitali Banerjee. Party diaries, 2023)
Priya Chakraborty plans a birthday party for her first client, Layla Aunty, personalizing everything from the invitations to the menu in Aunty's favorite color, but as party-time finally arrives, Priya is nervous something will go wrong.